Assessment of the performance of a historic minaret during the Kahramanmaras, earthquakes (Mw 7.7 and Mw 7.6) - Erkek, Hakan; Yetkin, Musa (Elsevier Science Inc, 2023)
On 6 February 2023, two devastating earthquakes with magnitudes Mw= 7.7 and Mw= 7.6 struck eastern Turkiye. These earthquakes caused thousands of houses to collapse and resulted in the deaths and injuries of thousands of people. Additionally, cultural heritage buildings were significantly impacted by the earthquakes. It was reported that 169 cultural heritage buildings were destroyed, and 535 buildings suffered severe damage in these earthquakes. This study focuses on a historic minaret severely damaged in the earthquakes. This study investigated the seismic performance of the historic Envar-ul Hamit Mosque, which suffered severe damage in the earthquakes on 6 February 2023. Firstly, laboratory experiments were conducted to determine the compressive strength of the historic minaret, followed by creating a finite element model for the minaret. The finite element model was refined based on the results obtained from an operational vibration test conducted on the historic minaret. Time history analyses were then performed using the updated finite element model. For seismic loading, acceleration records from Osmaniye station (station code: 8003) during the 6 February 2023 earthquakes (first shock, Mw=7.7) were utilized. Both horizontal components of the earthquake were applied to the historic minaret. Subsequently, these two horizontal components were rotated by 90 degrees and applied to the minaret again. Various response parameters were assessed, including peak displacement, base shear force, principal stresses, and plastic deformations. The results were then compared with the actual damage the historic building sustained.
Keywords: Kahramanmaras , earthquakes; Historic minaret; Operational vibration test; Laboratory experiments; Time history analyses